Foundations of Epidemiology - Bovbjerg, Marit L. (Open textbook library., 2019)
This book is intended to provide a basic introduction to epidemiologic methods and epidemiologic thinking. After reading this book, you should be able to read an epidemiologic study, understand what the authors did and why, and identify what they found. You will also have the tools to assess the quality of that study—how good is the evidence? What are potential sources of bias, and how might those have affected the results? This book will not teach you enough to be able to design and conduct your own epidemiologic studies—that level of understanding requires several years of specialized training. However, being able to read and understand the scientific literature about human health will allow you to apply that understanding to your own work in a nuanced, sophisticated way.